Reference manual for telecommunications engineering - Freeman, Roger L. (John Wiley & Sons, 2002)
Contains a compendium of the most frequently used data in day-to-day telecommunications engineering work: tables, graphs, figures, formulae, nomograms, performance curves, standards highlights, constants and statistics. Designed for easy and rapid access. Comprehensive reference for designing, building, purchasing, using or maintaining all kinds of telecommunications systems. Central source of information on transmission, switching, traffic engineering, numbering, signaling, noise, modulation and forward error correction.